Selective catalytic deoxygenation of palm oil to produce green diesel over Ni catalysts supported on ZrO2 and CeO2–ZrO2: Experimental and process simulation modelling studies - Tsiotsias, Anastasios I.; Hafeez, Sanaa; Charisiou, Nikolaos D.; Al-Salem, Sultan M.; Manos, George; Constantinou, Achilleas; Alkhoori, Sara; Sebastian, Victor; Hinder, Steven J.; Baker, Mark A.; Polychronopoulou, Kyriaki; Goula, Maria A. (My University, 2023)
The selective deoxygenation of palm oil to produce green diesel has been investigated over Ni catalysts supported on ZrO2 (Ni/Zr) and CeO2–ZrO2 (Ni/CeZr) supports. The modification of the support with CeO2 acted to improve the Ni dispersion and oxygen lability of the catalyst, while reducing the overall surface acidity. The Ni/CeZr catalyst exhibited higher triglyceride (TG) conversion and yield for the desirable C15–C18 hydrocarbons, as well as improved stability compared to the unmodified Ni/Zr catalyst, with TG conversion and C15–C18 yield remaining above 85% and 80% respectively during 20 h of continuous operation at 300 oC. The high C17 yields also revealed the dominance of the deCOx (decarbonylation/decarboxylation) pathway. A fully comprehensive process simulation model has been developed to validate the experimental findings in this study, and a very good validation with the experimental data has been demonstrated. The model was then further utilised to investigate the effects of temperature, H2 partial pressure, H2/oil feed ratio and LHSV. The model predicted that maximum triglyceride conversion was attainable at reaction conditions of 300 °C temperature, 30 bar H2 partial pressure, H2/oil of 1000 cm3/cm3 feed ratio and 1.2 h−1 LHSV.
Keywords: Ceria-zirconia; Computational fluid dynamics; Green diesel; Process modelling; Selective deoxygenation